EFFORTS TO INCREASE THE ACTIVITY AND ACHIEVEMENT OF LEARNING SCIENCE IN LIFETIME MATERIALS WITH STUDENT METAMORPHOSIS CLASS IV SDN 9 THROUGH METHODS EVERYONE IS TEACHER HERE SEMESTER 2 STUDY YEAR 2018/2019 - Nirmala Nirmala (Universitas Negeri Medan, 2020)
The purpose of this research is to increase student activeness and learning achievement in science learning life cycle material with metamorphosis using the Everyone is Teacher here method. This type of research is school action research which is carried out in 2 cycles and in each cycle consisting of 2 meetings with four stages, namely (1) planning, (2) implementation of action (action), 3) observation, ( 4) reflection (reflection). The research subjects were grade IV SDN 9 Melai with a total of 18 students. Data collection techniques using test techniques, observation and documentation. The data validation was done by triangulation. Data analysis used in this study was descriptive analysis of the percentage technique. The results showed that the increase in student activity in the initial study was only 6 students or 33.33%, increased to 12 students or 66.67% in the first cycle, and 100% or 18 students in the second cycle. This is also supported by the increase in student learning outcomes from the average in the initial study of only 57.78, up to 67.72 in the first cycle, and 77.22 in the second cycle, with a level of learning completeness of 3 students (16.67%) In the initial study, 66.67% or 12 students in the first cycle, 16 students or 88.89% in the second cycle, so it can be concluded that all indicators and criteria for the success of the learning improvement process have been met and achieved in the second cycle. From these data, it can be seen that the application of the one is teacher method is proven to increase the activeness and achievement of science learning in life materials with the fourth grade metamorphosis of SDN9 Melai semester 2 of the 2018/2019 academic year.Keywords: everyone is teacher here, activeness, learning achievement